Krisis Identitas Keilmuan Bahasa Arab Di Indonesia: Antara Ilmu Alat Dan Ilmu Tujuan - Irfan (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
Arabic language in Indonesia faces a profound epistemological crisis: it is simultaneously treated as an Instrumental Discipline (ilmu alat) to access Islamic texts and as an Autonomous Discipline (ilmu tujuan) worthy of study in its own right. This study critically examines this identity crisis through the lenses of Islamic educational epistemology, curriculum theory, and the sociology of knowledge. Employing critical library research methodology, the study analyzes the historical trajectory of Arabic language instruction in Indonesian Islamic educational institutions from pesantren traditions to state madrasah systems and identifies three core tensions: (1) the reduction of Arabic to a grammatical prerequisite rather than a living intellectual tradition; (2) the institutional fragmentation between ilmu alat and ilmu tujuan orientations across different types of educational institutions; and (3) the absence of a coherent national epistemological framework for Arabic language education. Drawing on key Indonesian scholars including Aziz Fachrurrozi, Acep Hermawan, Ahmad Fuad Effendy, and Amin Abdullah, as well as classical Islamic scholarship, this article proposes a reconceptualization of Arabic language identity in Indonesia through what is termed "Epistemological Integration" an approach that transcends the Instrumental Discipline/Autonomous Discipline binary by repositioning Arabic as both civilizational archive and living intellectual medium. The findings carry significant implications for curriculum policy, teacher education, and the institutional reform of Arabic language education in Indonesian Islamic schools and universities.